(untitled) (Revista Gestão & Conexões, 2023)
Organizational studies incorporate the political, socioeconomic and historical-cultural transformations of a nation. In the Brazilian context, such research brought greater autonomy through the work of Alberto Guerreiro Ramos, Maurício Tragtenberg and Fernando Claudio Prestes Mota, precursors of the ontoepistemological construction prior to the Anglo-Saxon criticism based on the administration mainstream. The study aims to conduct a systematic literature review on organizational studies in the Brazilian context that criticize Westernization in their theoretical construction and theorization, from 2018 to 2022. This review allowed mapping studies that bring a legitimized ideology for national theorization. The relevance of national researchers and the influence of their studies in Latin America and in the world contributed to a disentangling of dominant theories. Finally, the national constructs allowed a dialogue with the theme, and bequeathed pluriverse lenses in the analysis of discourses and contexts that keep Organizational studies in evidence.